EVALUASI EFEKTIFITAS SISTEM PEMUNGUTAN PAJAK BUMI DAN BANGUNAN DI KELURAHAN DIBAL KECAMATAN NGEMPLAK KABUPATEN BOYOLALI PROVINSI JAWA TENGAH - ENDANG MASITOH WAHYUNINGSIH, HENDRA HERMAWAN (MAJALAH ILMIAH GEMA, 2013)
Dibal Village is a government agency supervised by and accountable to the Chief of the Regional Head. One of the tasks given to the Sub Regional Head Tax was imposed by the Land and Building. Village plays an important role in the land and building tax voting to raise local revenues. Village have a system for collecting duties land and building tax.             The method used in this study is an interview with the submission of a list. Of questions to the collector land and building tax officials to obtain the required data, literature study aimed to obtain basic theory related to the United Nations collection, observation by observation and direct observation.             Evaluation shows state collection system that has been in the Village Dibal. Ranging from registration, reporting Marking, calculation and payment, but in its application occurs within the constraints imposed by the United Nations that the subject is not a resident of the Village Dibal. In order to maximize this result required the cooperation of other Sub premises concerned are subject to levy non-resident land and building tax Sub Dibal. From the results of polling conducted highly effective values ââobtained. In 2010 obtained the value of the effectiveness of  the effectiveness of 99%, in 2011 obtained a value of 103%, and in 2012 obtained a value of 101%. This indicates that the collection is done very well.   Keywords: land and building tax, collecting, effectiveness